2011
DOI: 10.1124/mol.111.071993
|View full text |Cite
|
Sign up to set email alerts
|

p38 Mitogen-Activated Protein Kinase-γ Inhibition by Long-Acting β2Adrenergic Agonists Reversed Steroid Insensitivity in Severe Asthma

Abstract: Corticosteroid insensitivity (CI) is a major barrier to treating severe asthma. Despite intensive research, the molecular mechanism of CI remains uncertain. The aim of this study was to determine abnormality in corticosteroid action in severe asthma and to identify the molecular mechanism of the longacting ␤ 2 -adrenergic agonists (LABAs) formoterol and salmeterol on restoration of corticosteroid sensitivity in severe asthma in vitro. Peripheral blood mononuclear cells (PBMCs) were obtained from 16 subjects wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
64
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 31 publications
(34 reference statements)
8
64
0
Order By: Relevance
“…In severe asthma, there appear to be multiple mechanisms that affect GR phosphorylation status, which could explain GC insensitivity seen in these patients. Increased p38 MAPK expression in PBMCs (24) or activity in PBMCs and alveolar macrophages (23,49) is associated with reduced patient sensitivity to GC therapy, possibly by driving GR phosphorylation on S226. The same group raised the hypothesis that decreased PP2A function could serve as a mechanism leading to GC insensitivity, in part via its failure to dephosphorylate GR on S226 residues (50).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In severe asthma, there appear to be multiple mechanisms that affect GR phosphorylation status, which could explain GC insensitivity seen in these patients. Increased p38 MAPK expression in PBMCs (24) or activity in PBMCs and alveolar macrophages (23,49) is associated with reduced patient sensitivity to GC therapy, possibly by driving GR phosphorylation on S226. The same group raised the hypothesis that decreased PP2A function could serve as a mechanism leading to GC insensitivity, in part via its failure to dephosphorylate GR on S226 residues (50).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies in immune cells suggested that the p38 MAPK-GR interaction acts as a novel mechanism driving GC resistance in patients with severe asthma (11). Indeed, the blockade of p38 MAPK pathways by soluble inhibitors (20,23) or by the longacting b agonists (LABAs) formoterol and salmeterol (24) was associated with a restoration of cell sensitivity to GC. Those reports identified p38 MAPK as an important kinase in peripheral blood mononuclear cells (PBMCs) that reduces GR functions by impairing GR nuclear translocation and/or DNA binding affinity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A PI3Kδ/γ inhibitor RV1729 has undergone early stage clinical evaluation in COPD, although no results are published (ClinicalTrials.gov Identifier: NCT02140346). The tricyclic antidepressant nortriptyline reverses corticosteroid insensitivity induced by oxidative stress in vitro by inhibition of PI3K-δ and it has been proposed as a potential treatment for corticosteroidinsensitivity in severe asthma, smokers with asthma and COPD [131]. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 inhaled dual PDE 3 and PDE 4 inhibitor, RPL554 has bronchodilator effects and is well tolerated in patients with asthma and COPD [140].…”
Section: Pi3kinase Inhibitorsmentioning
confidence: 99%
“…A PI3Kδ/γ inhibitor RV1729 has undergone early stage clinical evaluation in COPD, although no results are published (ClinicalTrials.gov Identifier: NCT02140346). The tricyclic antidepressant nortriptyline reverses corticosteroid insensitivity induced by oxidative stress in vitro by inhibition of PI3K-δ and it has been proposed as a potential treatment for corticosteroidinsensitivity in severe asthma, smokers with asthma and COPD [131]. …”
mentioning
confidence: 99%